Cultural capital, identity, and social mobility : the life course of working-class university graduates - Matthys, Mick.; Perlzweig, Naomi (New York : Routledge, 2013)
"This qualitative study explores the meaning of working-class origin in the life and career of university graduates. Social transition from a working-class background to a middle-class milieu results in loyalty conflicts and communication barriers. The lack of social and cultural capital and the absent sense of an assertive self-presentation are pivotal barriers to gaining management functions. Positions in certain key sectors are not necessarily allocated according to professional capacity, but to obscure social connections, regulated by cultural codes and tests. Matthys approaches social mobility as a trajectory of identity construction in which different classes are integrated, and uses the notion of identity capital to interpret and discuss the meaning of the individual drive in social mobility. "--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Social mobility; College graduates -- Social conditions; Working class -- Social conditions; Electronic books